Pervasiveness of ambulance etiquette and knowledge in general population: a perspective from Pakistan - Zehra, Fatima Tuz; Nisar, Diya; Zehra, Abeeha; Javed, Mahnoor; Usman, Mahnoor; Mahmood, Syed Uzair (International Journal Of Community Medicine And Public Health, 2020)
Background: Ambulance ethics refers to the principles of moral conduct that make the journey of an ambulance safe, convenient whereby ensuring provision of effective pre-hospital care to the patient. It concerns three sets of population: the paramedical staff, the patient and family and also the general population. Methods: Cross-sectional comparative study, conducted from February to May 2018. A questionnaire consisting of 25 questions was filled by 412 participants who were older than 15 years of age and their responses were collected via a 5-point likert scale. Chi-square analysis was done to compare the responses of medical and non-medical participants. Results: Vast majority of individuals agreed that they should give way to ambulances by switching their lanes or by breaking the signal. Half of the individuals were of the idea that ambulances should maintain their speed limit while some favored disregarding the speed limit if it meant saving someone’s life, while others remained neutral. A large percentage of participants agreed that a vehicle must meet certain standards in order for it to act as an ambulance. A number of participants agreed that an ambulance should have basic life support (BLS), the ambulance staff should be skilled enough to give cardiopulmonary resuscitation (CPR) en route to the hospital. Conclusions: The general population supports the idea that ambulances should have a hassle-free route to transport the patient to the hospital and to hasten the treatment even if that means breaking signals, switching lanes and exceeding speed limit.